Tectonic transition and extension at the eastern and western ends of the Altyn Tagh fault: insights from triple junctions - YI Kexin; JOLIVET Marc; GUO Zhaojie (Dizhi lixue xuebao)
Objective  The Altyn Tagh fault (ATF) is the largest left-lateral strike-slip fault on the northern margin of the Qinghai-Tibet Plateau, extending for about 1600 km. It accommodates a considerable portion of the India-Eurasia convergence and is widely regarded as a key tectonic boundary influencing the plateau’s uplift and outward growth. However, its mode of propagation remains debated. Resolving this debate requires clarifying how the ATF evolved into its present configuration and how it connects with adjacent structures such as the Qilian orogenic belt and the Qimantagh-Eastern Kunlun fault. In this study, we use the concept of triple junctions to investigate key transition zones at the eastern and western ends of the ATF—namely, the Subei and Tula triple junctions—to shed light on the fault’s Cenozoic segmented rupture and bidirectional extension.  Methods  Triple junction analysis, a fundamental method in plate tectonics, is utilized to assess fault properties and fault stability from a kinematic perspective. Additionally, GPS data and seismic source mechanism solutions are analyzed to characterize the current kinematic behaviors and movement directions of the faults.   Results  (1) Transition between ATF and Qilian orogenic belt: Subei triple junction. The central segment of the ATF was the earliest to become active during the Cenozoic, generating a compressional horsetail splay on its eastern termination. The Danghe Nanshan fault and Yemahe-Daxueshan fault emerged as part of this horsetail splay. As left-lateral strike-slip motion on the ATF accelerated in the Miocene, large offsets developed between the Tarim, Qaidam, and Qilian blocks, giving rise to a triple junction near Subei. Initially, this triple junction was unstable, and the Qilian block experienced extensional strain relative to the Tarim block, indicating a local stretching environment. To achieve stability, the ATF progressively “straightened” eastward, ultimately supplanting the Yemahe-Daxueshan fault. Its western segment was reoriented to run parallel to the ATF, while the Danghe Nanshan fault remained as the key boundary on the Qilian side. Consequently, a stable triple junction formed at the intersection of the ATF’s central and eastern segments with the Danghe Nanshan fault. At the present leading edge of the ATF’s eastward propagation, the Hongliuxia fault displays a similar evolutionary trajectory, suggesting that the ATF continues to extend by reconfiguring secondary faults. (2) Transition between ATF and Qimantagh-Eastern Kunlun fault: Tula triple junction. The ATF’s central segment spawned a tensional horsetail splay at its western termination, involving the Tula and Baiganhu faults. When large-scale activity on the Eastern Kunlun fault commenced in the Miocene, the Qaidam block began moving relative to the Eastern Kunlun block, producing an unstable triple junction in the Tula region. To achieve a stable configuration, the ATF propagated westward along a more linear path, gradually diminishing activity on the Baiganhu fault. As a result, the stable triple junction—involving the Tarim, Qaidam, and Eastern Kunlun blocks—ultimately localized where the ATF meets the Qimantagh-Eastern Kunlun fault. This westward “straightening” and the concurrent reduction in subsidiary fault activity have fashioned the current tectonic framework at the western end of the ATF.  Conclusion  (1) The ATF has undergone a segmented rupture–bidirectional extension process throughout the Cenozoic. (2) The Miocene activation of the Yemahe-Daxueshan, the Qimantagh-Eastern Kunlun and other fault systems led to the formation of two triple junctions at Subei and Tula, respectively. These junctions were initially unstable, prompting secondary faults to “shortcut” and realign and leading the ATF to straighten and extend farther east and west. [Significance] This study refines our understanding of how the Altyn Tagh fault expanded along the northern margin of the Qinghai-Tibet Plateau. By applying triple junction concepts to continental blocks, we illustrate how block interactions have governed the ATF’s segmentation and through-going evolution. The proposed segmented rupture–bidirectional extension framework reconciles geological observations of Cenozoic deformation along the ATF. It also underscores the importance of analyzing triple junctions in understanding large-scale tectonic reorganization.